Pattern of Dermatological Diseases in the Patients of Army Hospital, Kathmandu - Jha, Sagar Mani; Rajbhandari, Sudarsan Lal; Shakya, Nabinbhakta; Pokharel, Arbind; Jha, Beena (Medical Journal of Shree Birendra Hospital, 2010)
Introduction: Human Skin is the largest organ of the body and may mirror the presence of benign/ malignant systemic diseases in different ways. The pattern of Skin diseases vary in different parts of Nepal due to differences in socioeconomic and geographic factors. This retrospective study, pattern of skin disease in Army Hospital likely reflects the pattern of disease in the Kathmandu Valley. Aim: To study, assess and compare the different patterns of skin disease in the patients attending the outpatient department in the year 2007 and 2008 in the Army Hospital. Methods: This was a retrospective study and all the new cases which were diagnosed in the Department of Dermatology in the years 2007 and 2008 were included. The diseases were classified as Papulosquamous, Vesicobullous, Connectivetissue disorders, Skin and Soft tissue tumours, Infective, Eczema, Sexually Transmitted Disease (STI), Leprosy and those skin diseases which were not coming under this format were classified as others. Result: The total number of cases recorded in the Department of Dermatology were 16828 in the year 2007 and 18643 in 2008. It was found that the infective group of disorders were the largest group of disease, in the year 2007 a total of 6135 (36.4%) and in 2008 a total of 7883 (42.2%) had suffered from this group of disorders. And the incidence of infective disorder was also statistically significant when both the years were compared p-Value:0.00, OR:1.16, CI:1.11-1.21. Similarly other large groups were Eczema, papulosqumous and sexually tranmitted disease. Conclusion: It was found that the disease pattern in this study was lead by infective disease followed by eczema, papulosquamous disease and sexually transmitted disease. Key words: Eczema; Papulosquamous; Vesicobullous DOI: 10.3126/mjsbh.v9i1.3484 Medical Journal of Shree Birendra Hospital Vol.9(1) 2010 14-16